Sperm are promiscuous and CatSper is to blame… - Barratt, Christopher LR (Nature Publishing Group, 2012)
EMBO J 31 7, 1654–1665 02212012 A sperm-specific cation channel (CatSper) facilitates the entry of calcium necessary for rapid changes in sperm motility allowing the cell to navigate the hurdles of the female reproductive tract and successfully to locate the egg. Brenker and colleagues show that CatSper is (directly) activated by a diverse range of small organic molecules that are reported to evoke chemotaxis in human spermatozoa, suggesting that CatSper may function as a polymodal, chemosensory calcium channel. Additionally, they provide strong evidence that calcium entry into the spermatozoon does not employ specific, G protein-coupled odorant receptors or activation of trans-membrane adenylate cyclase and is not induced by cyclic nucleotides.